Cause, Pattern and Consequence of Understory Herbaceous Vegetation at a Foothill forest in Indian Eastern Himalaya - Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2014)
Herbaceous flora is the dynamic layer in a forest stratum that protects the soil and water regimes and improves productivity and soil fertility. Thus a study was conducted at Chilapatta Reserve Forest, West Bengal India to document the status of herb diversity, biomass and carbon accumulation. Stratified random nested quadrate sampling was adopted for analyzing the qualitative and quantitative characters. Forty nine herb species were recorded, of which seven are yet to be identified. Identified species were of 21 families and 36 genera. The herb diversity index, concentration of dominance, Shannon and Wiener index and evenness index was estimated as 0.62, 0.028, 4.46 and 2.27, respectively. Highest and lowest frequency was recorded 49.12 and 1.75 while relative frequency varied from 0.09 -1 to 1.87. Herb density ranged from 2 to 11193 individuals ha and relative density ranged from 0.05 to 1.76%. Most of the species were widely distributed and its abundance ranged from 0.80 to 12.76 while relative abundance ranged from 0.16 to 1.73%. IVI values ranged from 0.47 to 5.27. The above ground portion of herbs accumulated the major portion of biomass and carbon.